2018
DOI: 10.1080/02699931.2018.1526778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations versus stereotypes in emotion recognition: a replication and extension of Craig and Lipp’s (2018) study on facial age cues

Abstract: Recently, Cognition and Emotion published an article demonstrating that age cues affect the speed and accuracy of emotion recognition. The authors claimed that the observed effect of target age on emotion recognition is better explained by evaluative than stereotype associations. Although we agree with their conclusion, we believe that with the research method the authors employed, it was impossible to detect a stereotype effect to begin with. In the current research, we successfully replicate previous finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…If the task-irrelevant social cue moderates the speed and/or accuracy with which the task-relevant cue is categorized, this is taken as evidence of an interaction between these two cues. Using this method, it has been demonstrated that sex (Aguado et al, 2009; Becker et al, 2007; Craig & Lipp, 2017; Hugenberg & Sczesny, 2006), race (Bijlstra et al, 2010, 2014; Craig et al, 2012, 2017; Craig & Lipp, 2018a; Hugenberg, 2005; Lipp, Craig, & Dat, 2015), age (Bijlstra, Kleverwal, et al, 2019; Craig & Lipp, 2018a, 2018b), attractiveness (Lindeberg et al, 2019), and facial hair (Craig, et al, 2019) influence emotion perception.…”
Section: Simple Categorizationmentioning
confidence: 99%
“…If the task-irrelevant social cue moderates the speed and/or accuracy with which the task-relevant cue is categorized, this is taken as evidence of an interaction between these two cues. Using this method, it has been demonstrated that sex (Aguado et al, 2009; Becker et al, 2007; Craig & Lipp, 2017; Hugenberg & Sczesny, 2006), race (Bijlstra et al, 2010, 2014; Craig et al, 2012, 2017; Craig & Lipp, 2018a; Hugenberg, 2005; Lipp, Craig, & Dat, 2015), age (Bijlstra, Kleverwal, et al, 2019; Craig & Lipp, 2018a, 2018b), attractiveness (Lindeberg et al, 2019), and facial hair (Craig, et al, 2019) influence emotion perception.…”
Section: Simple Categorizationmentioning
confidence: 99%